2022
DOI: 10.1007/s00421-022-05055-6
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine/BDNF loss underscores narcosis cognitive impairment in divers: a proof of concept in a dry condition

Abstract: Purpose Divers can experience cognitive impairment due to inert gas narcosis (IGN) at depth. Brain-derived neurotrophic factor (BDNF) rules neuronal connectivity/metabolism to maintain cognitive function and protect tissues against oxidative stress (OxS). Dopamine and glutamate enhance BDNF bioavailability. Thus, we hypothesized that lower circulating BDNF levels (via lessened dopamine and/or glutamate release) underpin IGN in divers, while testing if BDNF loss is associated with increased OxS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…In recent years, our group has developed an Electron Paramagnetic Resonance (EPR) microinvasive method [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] capable of providing absolute ROS quantification using a drop of capillary blood taken from the fingertip. The small amount of blood requested for the analysis and the ease of the sample collection procedure makes this technique particularly suitable for performing repeated measures in a short time frame and thus for quantitatively monitoring the ROS response kinetics (on and off) to a particular stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group has developed an Electron Paramagnetic Resonance (EPR) microinvasive method [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] capable of providing absolute ROS quantification using a drop of capillary blood taken from the fingertip. The small amount of blood requested for the analysis and the ease of the sample collection procedure makes this technique particularly suitable for performing repeated measures in a short time frame and thus for quantitatively monitoring the ROS response kinetics (on and off) to a particular stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported a correlation between circulating BDNF levels and cognitive functions in healthy subjects but also those with various mental diseases ( 88 , 89 ). A very recent study in which a deep narcosis test was administrated via a dry dive test at 48 (meter sea water, msw) in a hyperbaric chamber to six well-trained divers showed that dopamine/BDNF loss underscores narcosis cognitive impairment in divers ( 90 ), but in that study, the initial BDNF values dropped for approximately 50%. Although decreases in BDNF levels after the first and third dives were mild and most probably a part of the physiological stress response, it would be worthful to explore if the observed changes in circulating BDNF levels are somehow related to divers' cognitive functions but also the levels of BDNF-releasing neurotransmitters, such as such as dopamine and glutamate.…”
Section: Discussionmentioning
confidence: 97%
“…An X-band electron paramagnetic resonance spectroscopy (EPR, 9.3 GHz) (E-Scan, Bruker Co., Billerica, MA, USA) was used to detect ROS production and TAC in saliva samples. Methods were previously described [ 29 , 30 , 32 , 33 , 34 ]; briefly, spin probe CMH (1-hydroxy-3-methoxy-carbonyl-2,2,5,5-tetramethylpyrrolidine) was used for ROS determination, and a stable radical CP (3-carboxy2,2,5,5-tetramethyl-1-pyrrolidi-nyloxy) was used as an external reference to convert ROS determinations into absolute quantitative values (μmol·min −1 ). Spin–trap 1,1-diphenyl-2-picrylhydrazyl (DPPH•) was used to measured TAC.…”
Section: Methodsmentioning
confidence: 99%